2020
DOI: 10.1021/acs.accounts.9b00496
|View full text |Cite
|
Sign up to set email alerts
|

CO2 Reduction: From Homogeneous to Heterogeneous Electrocatalysis

Abstract: Conspectus Due to increasing worldwide fossil fuel consumption, carbon dioxide levels have increased in the atmosphere with increasingly important impacts on the environment. Renewable and clean sources of energy have been proposed, including wind and solar, but they are intermittent and require efficient and scalable energy storage technologies. Electrochemical CO2 reduction reaction (CO2RR) provides a valuable approach in this area. It combines solar- or wind-generated electrical production with energy stora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
307
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 515 publications
(309 citation statements)
references
References 54 publications
1
307
0
1
Order By: Relevance
“…[20][21] Due to the high energy barrier and kinetic inertness of carbon dioxide, high-activity and high-selectivity catalytic substances are also required in electrochemical reduction to reduce reaction hindrance, which can increase the sufficient reaction rate of electrochemical reduction of carbon dioxide. [22] So the first task is to select the appropriate catalytic materials, which can increase the catalytic rate of carbon dioxide, while reducing the catalytic temperature.…”
Section: Introductionmentioning
confidence: 99%
“…[20][21] Due to the high energy barrier and kinetic inertness of carbon dioxide, high-activity and high-selectivity catalytic substances are also required in electrochemical reduction to reduce reaction hindrance, which can increase the sufficient reaction rate of electrochemical reduction of carbon dioxide. [22] So the first task is to select the appropriate catalytic materials, which can increase the catalytic rate of carbon dioxide, while reducing the catalytic temperature.…”
Section: Introductionmentioning
confidence: 99%
“…16 While there are a number of studies exploring ways to modify solid-state electrocatalysts, our program is intrigued by the use of molecular electrocatalysts to control reaction selectivity in flow cells because of the acute synthetic control over the electronic environment of the active site and the primary coordination and secondary coordination spheres. 3,[20][21][22][23][24] While we have shown that molecular electrocatalysts can operate at high current densities in a CO2RR flow cell for the selective formation of CO (i.e., FECO of 95% at 150 mA/cm 2 ), 25 the use of molecular electrocatalysts that reduce CO at high current densities under flow conditions has not yet been documented. 26,27 We report here that a copper phthalocyanine (CuPc; Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Catalyzing the CO 2 reduction reaction by electrochemical means offers an approach for converting this greenhouse gas into value-added chemical products with sustainable energy input. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] Efforts in molecular electrocatalysts for CO 2 reduction have predominantly focused on the 2electron/2-proton reduction of CO 2 into CO, which can then be fed into numerous existing industrial processes for chemical synthesis. Iron porphyrins, in particular, have been the subject of extensive research owing to their high selectivity for CO 2 versus proton reduction, structural tunability, and compatibility with various electrolyte media.…”
Section: Introductionmentioning
confidence: 99%